2003
DOI: 10.1210/me.2002-0392
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Corticotroph Ontogeny and Regulation in Transgenic Zebrafish

Abstract: We characterized zebrafish proopiomelanocortin (POMC) gene promoter, and sequence analysis revealed that the promoter contains regulatory elements conserved among vertebrate species. To monitor the ontogeny of the pituitary POMC lineage in living vertebrates, we generated transgenic zebrafish expressing green fluorescent protein (GFP) driven by the POMC promoter. Zebrafish POMC-GFP is first expressed asymmetrically as two bilateral groups of cells most anterior to the neural ridge midline at 18-20 h post ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 46 publications
12
113
0
Order By: Relevance
“…The pan-pituitary specification markers lim3 and pitx3 show reduced, but not completely abolished expression, while pit1 expression is completely absent (Pogoda et al, 2006b). This failure of pit1 activation is most likely the main reason for the later absence of prl, gh, and tsh- expression (see paragraph 9), whereas the absence of pomc expression might point to a direct role of Ascl1a as a transcriptional activator of pomc, consistent with the presence of E-boxes, consensus binding sites for bHLH proteins, in the promoter of the zebrafish pomc gene (Liu et al, 2003).…”
Section: Ascl1amentioning
confidence: 93%
See 2 more Smart Citations
“…The pan-pituitary specification markers lim3 and pitx3 show reduced, but not completely abolished expression, while pit1 expression is completely absent (Pogoda et al, 2006b). This failure of pit1 activation is most likely the main reason for the later absence of prl, gh, and tsh- expression (see paragraph 9), whereas the absence of pomc expression might point to a direct role of Ascl1a as a transcriptional activator of pomc, consistent with the presence of E-boxes, consensus binding sites for bHLH proteins, in the promoter of the zebrafish pomc gene (Liu et al, 2003).…”
Section: Ascl1amentioning
confidence: 93%
“…By trans-activating reporter assays it was shown that mouse Pitx1 can drive Lhx3 (the mouse homolog of zebrafish lim3) as well as prl and pomc expression (Lamonerie et al, 1996, Tremblay et al, 1998. Since Pitx binding sites have also been found in the zebrafish pomc promoter, and since lactotropes and corticotropes are the first differentiating AH cells of the zebrafish, one can speculate about a similar regulation of these genes by Pitx3 in teleosts (Liu et al, 2003).…”
Section: Pitx3mentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals, birds and other tetrapods have only one Pomc copy, but zebrafish and other teleosts, including fugu and Tetraodon nigroviridis, have two Pomc paralogues-pomca and pomcb-that date from the ancient whole-genome duplication in the teleost lineage around 320 Ma [51]. In zebrafish, pomca is expressed in the anterior and intermediate lobes of the pituitary as well as in the ventral hypothalamus, just like the tetrapod gene [52,53]. The expression pattern of zebrafish pomcb is unknown, but the Tetraodon homologue is expressed in the preoptic area of the brain and pituitary [51].…”
Section: (C) Evolution Of Pomc Transcriptional Expressionmentioning
confidence: 99%
“…In the mammalian pituitary, there is a large body of evidence that Pomc expression is regulated by several TFBSs present in the proximal promoter [54][55][56], as well as by a mammalian-conserved distal enhancer [57]. In the zebrafish, similar to mammals, it has been found that a construct carrying the proximal rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20130027 promoter and first intron of the pomca gene can drive green fluorescent protein (GFP) expression to the anterior and intermediate lobes of the pituitary, but not to ventral hypothalamic neurons [52]. A similar construct carrying 500 bp of the Xenopus laevis Pomc gene promoter directs GFP expression to cells of the intermediate lobe, but not the hypothalamus, of transgenic frog embryos [58], suggesting that the function of the proximal Pomc promoter in driving pituitary expression is ancestral in vertebrates.…”
Section: (C) Evolution Of Pomc Transcriptional Expressionmentioning
confidence: 99%